2021
DOI: 10.15698/cst2021.04.246
|View full text |Cite
|
Sign up to set email alerts
|

Roles of phosphatidyl inositol 3 kinase gamma (PI3Kγ) in respiratory diseases

Abstract: Phosphatidyl inositol 3 kinase gamma (PI3Kγ) is expressed in all the cell types that are involved in airway inflammation and disease, including not only leukocytes, but also structural cells, where it is expressed at very low levels under physiological conditions, while is significantly upregulated after stress. In the airways, PI3Kγ behaves as a trigger or a controller, depending on the pathological context. In this review, the contribution of PI3Kγ in a plethora of respiratory diseases, spanning from acute l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 117 publications
1
10
0
Order By: Relevance
“…1 ). Such a biphasic relationship between cardiac health and IIS-PI3K signaling activity reconciles previous opposing studies [ 6 ], [ 6 ], and suggests that partial inhibition of PI3K might be worth considering for the treatment of heart failure and other age-related chronic diseases – albeit at a much lower and safer dosage than that applied in cancer therapy [ 10 ], [ 11 ]. Alternatively, emerging autophagy inducers and caloric restriction mimetics, like spermidine and nicotinamide adenine dinucleotide (NAD + ) precursors [ 8 ], [ 12 ], [ 13 ], [ 14 ], might offer a readily-available, and perhaps safer, strategy for immediate testing in cardiac patients [ 15 ].…”
supporting
confidence: 78%
“…1 ). Such a biphasic relationship between cardiac health and IIS-PI3K signaling activity reconciles previous opposing studies [ 6 ], [ 6 ], and suggests that partial inhibition of PI3K might be worth considering for the treatment of heart failure and other age-related chronic diseases – albeit at a much lower and safer dosage than that applied in cancer therapy [ 10 ], [ 11 ]. Alternatively, emerging autophagy inducers and caloric restriction mimetics, like spermidine and nicotinamide adenine dinucleotide (NAD + ) precursors [ 8 ], [ 12 ], [ 13 ], [ 14 ], might offer a readily-available, and perhaps safer, strategy for immediate testing in cardiac patients [ 15 ].…”
supporting
confidence: 78%
“…The inhibition of PI3Kα/δ/β plays a key role in the inflammatory response to damage and infection (41,42). PI3K/Akt inhibition by compound 8C and PIK-75 has been shown to markedly decrease the production and biological activity of pro-inflammatory cytokines, such as TNF-α and IL-6 in a NF-κB-dependent manner (43,44), which is considered the central mediator of inflammatory process by inducing the expression of various pro-inflammatory genes (45,46). In the present study, it was found that LY294002 treatment inhibited the activation of the PI3K/Akt signal pathway, and decreased the upregulated expression of NF-κB, TNF-α and IL-1β in the spinal cords of rats with BCP.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring more molecular mechanisms involved in the reparative phase of ALI and determining optimal treatments is required to ameliorate EMT and lung fibrogenesis. PI3K represents a crucial signaling pathway during oxidative stress and fibrogenesis [ 14 , 35 ].…”
Section: Discussionmentioning
confidence: 99%